Is the practice of goal-setting for patients in acute stroke care patient-centred and what factors influence this? A qualitative study. (May 2016) - Rosewilliam, Sheeba; Sintler, Carron; Pandyan, Anand D; Skelton, John; Roskell, Carolyn A
Objective: To explore whether goal-setting for rehabilitation with acute stroke survivors is patient-centred and identify factors which influence the adoption of patient-centredness in goal-setting practice. Setting: Acute stroke unit in a large teaching hospital in England. Participants: Patients with stroke who had no cognitive or significant communication problems and health care professionals who had a significant engagement with an individual patient were approached for participation. Method: Multiple qualitative methods were used. Perceptions and beliefs about patient-centredness, within the context of goal-setting, were collected from patients and corresponding professionals using qualitative semi-structured interviews. Adoption of patient-centred behaviour was triangulated using analysis of patient records and observation of team meetings related to participating patients. Data analysis: Interview transcripts and field notes were coded, clustered under categories and descriptively summarised. Additionally, data from patients' documents were summarised. These summaries were then mapped on to an a-priori frame work of patient-centredness from which further interpretative themes were derived. Results: Seven patients and seven health-care professionals participated. Goal-setting was not consistently patient-centred as evidenced by a) incongruities between patients and professionals in setting, communicating and prioritising of goals and b) dysfunctional therapeutic relationships. The factors that influenced patient-centred goal-setting were both professional and patient beliefs and attributes, work-culture, practice model, limitations in knowledge and systems that disempowered both professionals and patients. Conclusion: It may be possible to infer that current local practice of goal-setting was inadequately patient-centred. Further research is required to identify strategies to overcome these challenges and to develop patient-centred goal-setting methods.